Effect of storage time, thermocycling and resin coating on durability of dentin bonding systems - Seyed-Mostafa Mousavinasab; Azadeh Farhadi; Mitra Shabanian (Wolters Kluwer Medknow Publications, 2009)
Background:Along with development of different dental adhesives, concerns about hydrolytic deg-radation of the adhesive components have arisen. The purpose of this study was to evaluate the in-vitro influence of thermocycling, water storage and resin coating on the microshear bond strength of total etch and self etch adhesive systems to dentin. Methods:The superficial coronal dentin of eighty intact third molars were exposed and divided into 5 equal groups. Dental adhesives including Scotch Bond Multi Purpose (SBMP), Single Bond (SB), Clearfil SE Bond (CSE), Prompt L-Pop (PLP), and Prompt L-Pop plus Margin bond (PLPM) were applied according to the manufacturers' instructions on prepared surfaces in the study groups, respectively. Then composite cylinders were bonded and specimens were divided into two subgroups. One subgroup was stored in water for 24 hours. The second subgroup was subjected to 3000 thermocycle shocks and then was stored in 37°C water for 3 months. Finally, all teeth were subjected to the mi-croshear bond strength test. Data were analyzed using two-way ANOVA and Tukey HSD tests. One specimen similar to each subgroup was also prepared for SEM evaluation. Results:After one-day storage, the SBMP showed the highest bond strength followed by CSE, PLPM, SB and PLP. After three months storage, the highest bond strength was observed in SBMP followed by PLPM, CSE, SB, and PLP. Conclusion: SBMP showed the best bond strength while CSE represented acceptable bond durabil-ity. Resin coating on PLP improved bond strength and durability.